Simulation and Fault Analysis using Reactive Energy Control for HVDC Line: Enhancing Protection Speed in HVDC Transmission Systems (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As we see modern civilization heavily depends on consumption of electrical energy for commercial, industrial, domestic, agricultural and social purposes. HVDC is most economical way to transmit bulk power over longer distances, complexity in controlling of the power flow, asynchronous power grid interconnections and due to its flexible power control. Among the numerous techniques concerning HVDC system, DC transmission line protection is one of the important unit thus it provides fast fault clearance and guarantees the operation security of the entire HVDC transmission system. In HVDC transmission lines uses the voltage differential protection in which voltage differential rate to identify the faults takes place on transmission line but this technique not efficient due to not detect high impedance faults and its sensitivity to faults resistance. This paper proposes a novel directional protection scheme based on reactive energy for HVDC transmission systems. In this paper reactive energy is defined as the integral of reactive power during a period of time. The Hilbert transform is employed to continuously calculate the reactive energy, and then, the reactive energy flow directions are applied to identify internal and external faults. Compared to the traditional current differential scheme, this protection has a smaller time delay, thus significantly increasing the protection speed.